1998
DOI: 10.2307/1132369
|View full text |Cite
|
Sign up to set email alerts
|

Similarities between Friends and Nonfriends in Middle Childhood

Abstract: Similarities were assessed between target children (mean age, 11.1 years) and their friends and nonfriends, respectively. One target child of each sex (N = 192), along with one same-sex friend and one nonfriend, were selected from 102 participating classrooms. "Guess who" nominations obtained within these classrooms were used to measure prosocial behavior, antisocial behavior, shyness / dependency, and sociometric status; selfreports were used to measure depressive symptoms. Children and their friends were mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
101
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 15 publications
11
101
1
9
Order By: Relevance
“…Importantly, these findings also provide support for the "reputationalsalience hypothesis," or the notion that similarities between friends vary according to the salience of the attribute in determining the social reputations of the children involved (Haselager et al, 1998). In other words, it would be expected that aggressive children would be more likely to have friends who were highly aggressive, and withdrawn children would have friends who were highly withdrawn because such similarities would be consistent with their reputations.…”
Section: Who Do Shy and Socially Withdrawn Children Befriend?supporting
confidence: 58%
See 3 more Smart Citations
“…Importantly, these findings also provide support for the "reputationalsalience hypothesis," or the notion that similarities between friends vary according to the salience of the attribute in determining the social reputations of the children involved (Haselager et al, 1998). In other words, it would be expected that aggressive children would be more likely to have friends who were highly aggressive, and withdrawn children would have friends who were highly withdrawn because such similarities would be consistent with their reputations.…”
Section: Who Do Shy and Socially Withdrawn Children Befriend?supporting
confidence: 58%
“…Specifically, they posited that friendship might function protectively when children are similar to their friends in terms of prosocial tendencies. Alternatively, friendship can be a risk factor when there are behavioral concordances in aggression and displays of antisocial behaviors, a view that has been supported in empirical studies by Dishion and colleagues (e.g., Dishion, Andrews, & Crosby, 1995).Importantly, these findings also provide support for the "reputationalsalience hypothesis," or the notion that similarities between friends vary according to the salience of the attribute in determining the social reputations of the children involved (Haselager et al, 1998). In other words, it would be expected that aggressive children would be more likely to have friends who were highly aggressive, and withdrawn children would have friends who were highly withdrawn because such similarities would be consistent with their reputations.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Anxious solitary children may have friends with similar behavioral tendencies. Indeed, evidence indicates that children tend to become friends with peers with whom they share behavioral characteristics (homophily) (Farver, 1996;Haselager, Hartup, van Lieshout, & Riksen-Walraven, 1998;Hogue & Steinberg, 1995;Rubin, Lynch, Coplan, Rose-Krasnor, & Booth, 1994). Although this effect has most often been demonstrated for conconcordance in aggressive behavior (Farver, 1996;Hanish, Martin, Fabes, Leonard, & Herzog, 2005), Rubin and colleagues have demonstrated that children develop preferences for interacting with playmates who resemble themselves with respect to rate of solitary behavior ; see also French, Jansen, Riansari, & Setiono, 2003;Haselager et al, 1998).…”
Section: Friends' Characteristicsmentioning
confidence: 99%